Remote laboratory: an analysis of the theses and dissertations database (Research, Society and Development, 2022)
This research is of the state of knowledge type and aims to analyze and infer about academic research with the theme of remote laboratory. The research of works with this theme was carried out in the Bank of Theses and Dissertations of CAPES, covering the period from 2015 to 2021. 5 theses and 28 dissertations were selected and analyzed, in order to know the number of researches that have already been carried out in the postgraduate courses, as well as their trends, types of research, methodologies and theoretical foundations comprising the proposed theme. We can observe the absence of important information in most of the analyzed works, which we call “non-specific”. The works using the remote laboratory as a research object in the teaching area are scarce and there is still much to be researched. Thus, state-of-the-art works provide an overview of what was researched, showing gaps, possibilities, saturations and, therefore, direct and guide future research.